الاطار القانوني الجديد للاستثمار الاجنبي في الجزائر - مخزوني فؤاد; بالمسعود مطيرة; بالمسعود صفية (My University, 2023)
تتمثل الاجهزة القانونية لتأطري الاستثمار في ظل القانون الجديد رقم ،18-22 في الوكالة الجزائرية لترقية الاستثمار التي حلت محل الوكالة الوطنية لترقية الاستثمار المنشأة بموجب أحكام للمادة 6 من الامر رقم 03-01 مؤرخ في 20 أوت 2001 يتعلق بتطوير الاستثمار، تتمتع بمهام وصلاحيات واسعة، سواء في جمال الاعلام، والتسهيل على المستثمرين عن طريق المنصة الرقمية، أو في جمال ترقية الاستثمار والمبادرة بكل نشاط مع الهيئات العمومية، ومرافقة المستثمر عن طريق التوجيه والتكفل بالمستثمرين، وكذا في جمال تسيري الامتيازات وإجراءات المتابعة. وفي المجلس الوطني للاستثمار المنشأ بموجب أحكام الامر رقم 03-01 الملغىوتم الابقاء عليه في ظل القانون الجديد، يتمتع بسلطات محددة وهي اقتراحاستراتيجية الاستثمار، وتنسيقها والعمل على تنفيذها، ويعد تقريرا سنويا يرفعه لرئيس الجمهورية يوضع لدى الوزير الاول أو رئيس الحكومة حسب الحالة.Summary: The legal bodies for investment management under the new Law No. 18-22 are represented by the Algerian Agency for Investment Promotion, which replaced the National Agency for Investment Promotion established under the provisions of Article 6 of Ordinance No. 03-01 dated August 20, 2001 related to investment development. It has broad tasks and powers. Whether in the beauty of information, facilitating investors through the digital platform, or in the beauty of promoting investment and initiating every activity with public bodies, and accompanying the investor by directing and sponsoring investors, as well as in the beauty of facilitating privileges and follow-up procedures. In the National Investment Council established under the provisions of Order No. 01-03, which was canceled and was retained under the new law, it has specific powers, which are proposing the investment strategy, coordinating it and working on its implementation, and prepares an annual report to be submitted to the President of the Republic, which is placed with the Prime Minister or the Prime Minister, as the case may be.
مذكرة ماستر
Keywords: الاستثمار الأجنبي – الجودة – الوكالة – المستثمر.: foreign investment - quality - agency - investor.